RISKS OF INTERACTION BETWEEN GOVERNMENT BODIES AND BUISNESS STRUCTURES IN THE RUSSIAN AGRICULTURAL SECTOR - Ivanovich Gayduk, Vladimir; Dmitrievich Kovalchuk, Maksim; Аlekseyevich Еrmakov, Аleksey; Yurievna Kamysheva, Svetlana (Revista Inclusiones, 2019)
This article aims to provide a justification of the risks of interaction between government bodies and business structures in the agricultural sector. For modern society, the scientific study of entrepreneurship is characterized by an extremely wide range of theoretical and methodological approaches. The purpose of this study is to improve the methodological support for the interaction of government bodies and business structures in the agricultural sector. Following the goal, the authors concentrated on the following objectives. They have investigated the most significant obstacles that hinder the formation, functioning, and development of Russian entrepreneurship in the agricultural sector and studied an approach that views interaction risks as a measure of deviation from the goals of society, business, and entrepreneurship. The authors have also developed a proposal on understanding the problem of harmonizing the goals of economic macrosystem entities and the relationships describing this problem, as well as studied the potential for managing the main risks of interaction between government bodies and business structures, based on which they have made proposals for implementation. Practical implementation of the theoretical results obtained allows to develop and improve the mechanism for managing the interaction between government bodies and business structures in the agricultural sector, considering the associated risks, simulating public policy in the field of public-private partnership, and reducing risks for participants of this kind of partnerships and projects in general.